2007
DOI: 10.1094/pdis-91-6-0767c
|View full text |Cite
|
Sign up to set email alerts
|

Association of Burkholderia glumae and B. gladioli with Panicle Blight Symptoms on Rice in Panama

Abstract: Panicle blight of rice, caused by Burkholderia glumae, has been a serious problem on rice in Japan since 1955. It has been reported from other rice-producing countries around the world and recently was reported on rice in the southern United States (2). A rice producer in Panama contacted us to verify the occurrence of bacterial panicle blight in rice fields where heavy losses were associated with a disease of unknown etiology, but with typical bacterial panicle blight symptoms (2). The observed grain discolor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 0 publications
2
21
0
Order By: Relevance
“…Although rice grain rot, caused by B. glumae (formerly Pseudomonas glumae), was initially considered a serious pathogen only in Japan, it is now reported in several major rice growing countries of the world including Korea (10), Taiwan (2), Latin America (21,40), Vietnam (33), the Philippines (3), and the Gulf of Mexico rice production area in the United States (20,22,27,30). The pathogen was reported in 2007 from symptomless seeds in China, where the isolated strain caused disease in inoculated rice plants (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although rice grain rot, caused by B. glumae (formerly Pseudomonas glumae), was initially considered a serious pathogen only in Japan, it is now reported in several major rice growing countries of the world including Korea (10), Taiwan (2), Latin America (21,40), Vietnam (33), the Philippines (3), and the Gulf of Mexico rice production area in the United States (20,22,27,30). The pathogen was reported in 2007 from symptomless seeds in China, where the isolated strain caused disease in inoculated rice plants (17).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, real-time PCR assays have been used for rapid, accurate, and sensitive identification and quantification of pathogens from infected plant tissues (15,16,24,29). PCR and real-time PCR have been used as the main methods for identifying several Burkholderia species from soil, water, infected plants, and mammalian cells (5,18,21,22,27,32). In our study, we screened all of the rice strains with B. glumae-specific primers and then screened B. glumae-negative strains with B. gladioli-, B. plantarii-, and B. multivorans-specific primers.…”
Section: Discussionmentioning
confidence: 99%
“…The infection reduces yield owing to spikelet abortion, and infected seeds cause BSR and grain rot in the next generation (Ham et al 2011b). BSR and bacterial grain rot have been widespread in Japan (Goto and Ohata 1956; Goto et al 1987; Kurita and Tabei 1967; Uematsu et al 1976a), East Asia (Azegami 2009; Chien and Chang 1987; Cottyn et al 1996a, b; Jeong et al 2003; Luo et al 2007; Trung et al 1993) and Latin America (Nandakumar et al 2007b; Zeigler and Alvarez 1989). Therefore, it is necessary to breed cultivars, which are resistant to both BSR and bacterial grain rot.…”
Section: Discussionmentioning
confidence: 99%
“…Since disease caused by B. glumae was first discovered in Japan (Goto and Ohata 1956; Goto et al 1987; Kurita and Tabei 1967; Uematsu et al 1976a), it has also been reported in other countries in East Asia (Azegami 2009; Chien and Chang 1987; Cottyn et al 1996a; Cottyn et al 1996b; Jeong et al 2003; Luo et al 2007; Trung et al 1993) and Latin America (Nandakumar et al 2007b; Zeigler and Alvarez 1989). In the USA, B. glumae has been identified as the major causal agent of bacterial grain rot (Nandakumar et al 2005, 2009; Shahjahan et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…As a phytopathogen, plant-associated Burkholderia spp. are very important because they cause heavy damage and rapidly spread to many countries (Ura et al 2006;Nandakumar et al 2007Nandakumar et al , 2009Riera-Ruiz et al 2014). For example, B. plantarii causes seedling blight in rice through its phytotoxin tropolone (Urakami et al 1994).…”
Section: Introductionmentioning
confidence: 99%